Perspectives on "Community" with Inuit Living in Southern Quebec. Issue 3 (3rd July 2022) - Lapointe, Mathilde; Boucher, Nathalie; Benoit, Ariane; Fletcher, Christopher
ABSTRACT: What is a community? This seemingly simple question emerged at the outset of the Qanuikkat Siqinirmiut? (QS) research project on Inuit health in southern Quebec, led in partnership with the Southern Quebec Inuit Association. The question finds its salience in the rapid growth of a southern Inuit population in cities across Canada, a population that has distinct and significant health needs. After early qualitative research, we came to doubt whether the term community adequately characterizes the situation of the roughly 2, 000 Inuit living in the South. Thus, this article examines the discourse of community. Specifically, we present an analysis of two schools of thought on the subject: first, the notion of community from classic academic work in urban geography by the Chicago School; and second, inuuqatigiitsiarniq (living well together), which comes from an Inuit system of values and model of health. We first describe the ethnographic data upon which our analysis is drawn and introduce key concepts. Then, we identify conceptual shortcomings in the Chicago School's notion of community and describe how inuuqatigiitsiarniq expands and nuances the concept. Finally, we discuss the potential of using both concepts to foster a refined understanding of relational health for Inuit living in Montreal.